Psychosomatics in ophthalmology - review of the literature - Hyjek, Michał; Marczak, Aleksandra; Hordejuk, Michalina; Szymkiewicz, Karolina (Journal of Education, Health and Sport, 2022)
Objective: This study aimed to demonstrate the potential influence of psychiatric disorders on the development and course of ophthalmic diseases. Methods: A literature search was performed in the PubMed medical publication database using the following keywords: ophthalmology; glaucoma; psychiatrists; psychology; acute anterior uveitis; psychosomatics; health. Results: Stress and psychiatric disorders are underestimated risk factors in the course of ophthalmic diseases. Understanding the relationship between them is crucial to ensuring proper patient care. This is because vision loss has serious consequences for the patient, ranging from difficulties in everyday life to disability, loss of livelihood and dependence on others. The stress reaction is associated with long-term persistence of high cortisol levels, stimulation of the autonomic system and, consequently, vascular dysregulation and neuropathy. The result is a progression of visual disturbances, which causes further stress and anxiety. Conclusions: Effective psychiatric intervention, the correct physician approach, or relaxation techniques can speed up recovery or reduce the risk of recurrence.